ANALISIS KOLOM BETON BERTULANG PADA PENAMPANG PERSEGI BERLUBANG - Nasution, Amrun; Islam, Mukhlis (Universitas Bengkulu, 2019)
Installation of the pipe in the column (conduit) such as electrical and sanitary plumbing installations are found in the structure of reinforced concrete columns. This causes it to be a hollow column. The existence of holes cause a reduction in cross sectional area of the column and can result in reduced strength of a column. The purpose of this study was to know the power difference hollow concrete columns with concrete columns are not hollow and produce an analysis of the interaction in the form graphics axial force (Pn) and nominal torque (Mn). The analytical method developed by using square column spread sheet applications and use the stress-strain relationship hognestad. Analysis of the hollow square column in this study as many as 720 samples. This study used 300x300-600x600 mm dimensions with an increase of 100 mm. Quality concrete (f'c) used was 25-30 MPa to 2.5 MPa rise. Quality reinforcement (fy) used was 400 MPa and the ratio of the reinforcement taken from 1% -8% with an increase of 2% of the cross sectional area of the column, with the amount of reinforcement as much as 12-20 pieces of reinforcement to rise 4 pieces. Widely used hole that is 3% -7%, with an increase of 1%. The analysis showed a decrease in Pn-Mn hollow column to column was not perforated. The decrease Pn maximum of 7.20% in the area of hole 7% by eccentricity to d amounting to 8.01% and the maximum Mn decrease of 10.91% in the area of hole 7% by eccentricity to d amounting to 20.51%.